Diabetes induced by checkpoint inhibition in nonobese diabetic mice can be prevented or reversed by a JAK1/JAK2 inhibitor. Issue 11 (30th October 2022) - Ge, Tingting; Phung, Amber‐Lee; Jhala, Gaurang; Trivedi, Prerak; Principe, Nicola; De George, David J; Pappas, Evan G; Litwak, Sara; Sanz‐Villanueva, Laura; Catterall, Tara; Fynch, Stacey; Boon, Louis; et al.
Abstract: Objectives: Immune checkpoint inhibitors have achieved clinical success in cancer treatment, but this treatment causes immune‐related adverse events, including type 1 diabetes (T1D). Our aim was to test whether a JAK1/JAK2 inhibitor, effective at treating spontaneous autoimmune diabetes in nonobese diabetic (NOD) mice, can prevent diabetes secondary to PD‐L1 blockade. Methods: Anti‐PD‐L1 antibody was injected into NOD mice to induce diabetes, and JAK1/JAK2 inhibitor LN3103801 was administered by oral gavage to prevent diabetes. Flow cytometry was used to study T cells and beta cells. Mesothelioma cells were inoculated into BALB/c mice to induce a transplantable tumour model. Results: Anti‐PD‐L1‐induced diabetes was associated with increased immune cell infiltration in the islets and upregulated MHC class I on islet cells. Anti‐PD‐L1 administration significantly increased islet T cell proliferation and islet‐specific CD8 + T cell numbers in peripheral lymphoid organs. JAK1/JAK2 inhibitor treatment blocked IFNγ‐mediated MHC class I upregulation on beta cells and T cell proliferation mediated by cytokines that use the common γ chain receptor. As a result, anti‐PD‐L1‐induced diabetes was prevented by JAK1/JAK2 inhibitor administered before or after checkpoint inhibitor therapy. Diabetes was also reversed when the JAK1/JAK2 inhibitor was administered after the onset of anti‐PD‐L1‐induced hyperglycaemia. Furthermore, JAK1/JAK2 inhibitor intervention after checkpoint inhibitors did not reverse or abrogate the antitumour effects in a transplantable tumour model. Conclusion: A JAK1/JAK2 inhibitor can prevent and reverse anti‐PD‐L1‐induced diabetes by blocking IFNγ and γc cytokine activities. Our study provides preclinical validation of JAK1/JAK2 inhibitor use in checkpoint inhibitor‐induced diabetes. Abstract : Type 1 diabetes is a side effect of immune checkpoint inhibitor therapy for cancer. Here, we show that a JAK1/JAK2 inhibitor can prevent and reverse anti‐PD‐L1‐induced diabetes in NOD mice by blocking common gamma chain cytokine activities in T cells and interferon‐gamma function on beta cells. This study provides preclinical validation of the use of JAK inhibitors in checkpoint inhibitor‐induced diabetes.